Measurement Methods Effects on the Swithing Behaviour of Sputtered Titania Thin Films - Syahirah Kamarozaman, Nur; Hana Herman, Sukreen; Abu Bakar, Raudah; Uzair Shamsul, Muhammad; Hikmee Mahzan, Norhidayatul; Bakhtiar Hashim, Shaiful (International Journal of Engineering and Technology, 2018)
The paper presents the issues regarding on the effect of measurement methods to the memristive behaviour to get a reliable and repeatable data. The measurement methods include the measurement cycles and different direction of bias voltage applied to the sample. A one layer of titania thin films was deposited sandwiched between Pt and ITO substrate to form metal-insulator-metal (MIM) structure which is the fundamental structure of memristive device. The oxygen flow rate was varied to 10, 20 and 30% during deposition process of sputtering method. The measurement cycles was repeated for three times. It was found that the device with thinner film required lesser time to get a repeatable I-V curve compared to the device with thicker film. The memristive behaviour is depended on ions movement either positively charged oxygen vacancies or negatively charged excess of oxygen ions. Thus, starting the voltage sweeps either positive or negative voltage applied to the sample is studied in this work. The oxygen vacancies movement in the active layer is proposed.Â Â